2021
DOI: 10.21664/2238-8869.2021v10i2.p261-281
|View full text |Cite
|
Sign up to set email alerts
|

Formación Académica del Ápice Estratégico de las Universidades Estatales en Chile

Abstract: Las universidades son consideradas el ejemplo paradigmático de las instituciones del conocimiento, por lo mismo, se espera que estas sean lideradas por personas con las mayores competencias directivas y académicas disponibles. En este sentido, el estudio tiene como propósito cardinal describir la gestión de conocimiento vinculado a la formación académica del ápice estratégico de universidades estatales chilenas, con el objeto de orientar la definición de políticas respecto de los requisitos formales que se deb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…In particular, this research, considering only private universities ascribed to the Admission System, identified a significant gender gap and inequality in managerial positions, given that women hold only 8.5% of these. The disaggregated data in Table 3 shows there are no female university chancellors, a situation that is not too far from what occurs in state universities where there was only one female chancellor up to 2020 (Ganga-Contreras et al 2021). As for the second level, there is only one female provost, and in the vice chancellor's offices, women occupy only 9.8% of these positions, well below the state universities, where 25% of the positions of chancellors, provosts, and vice chancellors are held by women (Ganga-Contreras et al 2021).…”
Section: Gendermentioning
confidence: 84%
See 3 more Smart Citations
“…In particular, this research, considering only private universities ascribed to the Admission System, identified a significant gender gap and inequality in managerial positions, given that women hold only 8.5% of these. The disaggregated data in Table 3 shows there are no female university chancellors, a situation that is not too far from what occurs in state universities where there was only one female chancellor up to 2020 (Ganga-Contreras et al 2021). As for the second level, there is only one female provost, and in the vice chancellor's offices, women occupy only 9.8% of these positions, well below the state universities, where 25% of the positions of chancellors, provosts, and vice chancellors are held by women (Ganga-Contreras et al 2021).…”
Section: Gendermentioning
confidence: 84%
“…It is interesting to mention that only 36.36% of the total number of chancellor's offices analyzed have a doctorate degree and a similar percentage have a master's degree, the remaining percentage are cases with no information. When compared with state universities, we find that 55.6% of the Chancellors have a doctorate degree and 65% hold a Master's degree (Ganga-Contreras et al 2021). In the provosts' offices, the doctorate predominates (half of them have this degree), followed by the master's degree and bachelor's degree, both at 25%.…”
Section: Academic Degreementioning
confidence: 92%
See 2 more Smart Citations
“…Competencias directivas en una universidad de la Zona Central de Chile. Journal of the Academy, 6, 48-65. https://doi.org/10.47058/joa6.4educación superior altamente preparados y comprometidos darán el paso que se requiere hacia una adaptación en escenarios cambiantes(Abello-Romero et al, 2021;Acosta-Silva et al, 2021;Fossatti et al, 2017;Ganga-Contreras et al, 2021;Wandercil et al, 2021).Las competencias directivas son el conjunto de conocimientos, habilidades y actitudes que debe poseer un directivo, las cuales le permitirán alcanzar el éxito en el desempeño de sus funciones(Martínez et al, 2016). En este sentido, los directivos tienen un rol fundamental en el éxito o fracaso de las instituciones, propiciar la calidad y generar las condiciones para el proceso de acreditación de toda institución(Aristimuño et al, 2011; Núñez-Rojas y Díaz-Castillo, 2017).…”
unclassified